IMPROVING METHODS OF TRAINING FUTURE DEFECTOLOGISTS IN DESIGNING CORRECTIONAL WORK (American Journal of Interdisciplinary Research and Development, 2024)
This article describes the improvement of methods for training future teachers of the deaf in the construction of correctional work, the particular relevance of the problem of early support for children with hearing impairment, and the systematic training of senior students in correctional work for children of different ages. ages and technologies of pedagogical work, focused on the need to form knowledge. To do this, it is necessary to plan various professional tasks of the teacher of the deaf - diagnostic, methodological, psychological, correctional, social work, which can make it possible to understand and assess the level of readiness of the future speech of the teacher of the deaf for independent professional activities.